Do Different Types of Innovation Require Specific Kinds of Knowledge Links? - Franz Toedtling; Patrick Lehner (European Regional Science Association (ERSA), 2006)
Innovations are increasingly seen as result of an interactive process of knowledge generation and knowledge application. According to the innovation systems model the business sector, the science sector, and policy actors are involved in this process. What is often neglected in existing literature is the aspect that different kinds of innovation may require specific types of relations. Radical innovations often draw on new scientific knowledge generated in universities and research organizations. The exchange of this type of knowledge requires intensive personal interactions and thus might favor local / regional levels over others. Incremental innovations on the other hand are often taking place in interaction with customers and suppliers which are often located at higher spatial levels beyond the region. In the present paper we will analyze the relationship between the different kinds of innovation and the respective knowledge links – characterized by the type and location of innovation partners as well as by the mode of knowledge exchange. Preliminary results show that firms introducing products new to the market are relying to a higher degree on patents and they are cooperating with universities and research institutes. Hereby, researchers seem to exert a bridging function between the business and the science sector. The mode of knowledge exchange seems to be also influenced by location. Knowledge between geographically close science and industry partners is exchanged through cooperation, whereas over longer distances knowledge is more often acquired by contract research.
Keywords: 330